Ongoing Lithospheric Alteration of the North China Craton Revealed by Surface‐Wave Tomography and Geodetic Observations - J. K. Feng; H. J. Yao; L. Chen; C. L. Li (Geophysical Research Letters)
Abstract The North China Craton (NCC) is renowned for cratonic reactivation and dramatic destruction. Detailed lithospheric structure is crucial for understanding the geological evolution and seismogenesis of the NCC. We imaged the lithospheric structure of the central and eastern NCC with ambient noise and teleseismic surface wave tomography. Our new model unveils remarkable N‐S variation in the lithospheric structure. An E‐W elongated lithospheric weak zone, coinciding with contemporary left‐lateral shearing revealed by geodetic observation, occupies the northern central and eastern NCC. Our model suggests that radical destruction of the eastern NCC in the late Mesozoic facilitated the late‐Cenozoic shearing induced by the continuous India‐Eurasia convergence. The late‐Cenozoic shearing progressively altered the pre‐thinned lithosphere accompanied by asthenospheric upwelling and strong seismic activity. Our results suggest a transition from the Pacific subduction dominating tectonic regime to the India‐Asia collision dominating lithospheric deformation framework in the Cenozoic and ongoing lithospheric alteration of the NCC.